17β-Estradiol Stimulates Resistin Gene Expression in 3T3-L1 Adipocytes via the Estrogen Receptor, Extracellularly Regulated Kinase, and CCAAT/Enhancer Binding Protein-α Pathways - Chen, Yen-Hang; Lee, Meng-Jung; Chang, Hsin-Huei; Hung, Pei-Fang; Kao, Yung-Hsi (Endocrinology (Philadelphia), 2006)
Resistin is known as an adipocyte-specific secretory hormone that can cause insulin resistance and decrease adipocyte differentiation. It can be regulated by sexual hormones, but the mechanism of estrogen’s actions is still not clear. Using 3T3-L1 adipocytes, we found that 17β-estradiol (E2) up-regulated resistin mRNA expression in a dose- and time-dependent manner. The concentration of E2 that increased resistin mRNA levels by 100–250% was approximately 1 nm for a range of 1–24 h of treatment. Treatment with either actinomycin D or cycloheximide prevented E2-stimulated resistin mRNA expression, suggesting that the effect of E2 requires new mRNA and protein synthesis. Although E2 was shown to increase activities of the estrogen receptor (ER) and MAPK kinase 1 and the association of nuclear ERα and CCAAT/enhancer binding protein-α with the resistin gene promoter, signaling was demonstrated to be blocked by pretreatment with either ICI182780 or PD98059. Neither SB203580 nor LY294002 changed the E2-increased levels of resistin mRNA, but they respectively inhibited E2-stimulated phosphorylation of p38 MAPK and Akt. These results imply the ERα, ERK, and CCAAT/enhancer binding protein-α are necessary for the E2 stimulation of transcription from the resistin promoter. Moreover, PD98059, but not SB203580 or LY294002, antagonized E2-increased resistin protein release. These data suggest that E2 likely modifies the distribution of the resistin protein between the intracellular and extracellular compartments via an ERK-dependent pathway.